Developing a financial profile test : big five personality traits and degree of financial literacy influencing individual financial risk tolerance - Schwar, Juliane Katharina (2024)
In "Developing a Financial Profile Test: Big Five Personality Traits and Degree of Financial Literacy Influencing Individual Financial Risk Tolerance" by Juliane Schwar, the focus is on creating a financial profile test to assess an individual9s financial risk tolerance influenced by personality traits and financial literacy. The research builds on existing studies showing that financial risk tolerance is complex and influenced by several factors. The study highlights a common discrepancy between people's perceived financial knowledge and their actual understanding. To address this, the study measures financial literacy by combining self assessment with questions on diverse financial topics. Personality traits are assessed through questions built on the Big Five personality traits: openness, conscientiousness, extraversion, agreeableness, and neuroticism. Financial risk tolerance is measured using a questionnaire designed to explore various aspects of this trait. Based on their answers, people are grouped into several profiles using cluster analysis. Contrary to previous investigations, conscientiousness is found to positively influence risk tolerance, while openness to experiences has no significant impact. The study ultimately distinguishes individuals into seven risk tolerance clusters, integrating financial literacy and personality traits.